Adaptive Memory of Human NK-like CD8+ T-Cells to Aging, and Viral and Tumor Antigens - Pita-López, María Luisa; Pera, Alejandra; Solana, Rafael (Frontiers in Immunology, 2016)
Human NK-like CD8+ T-cells are singular T-cells that express both T and NK cell markers such as CD56; their frequencies depend on their differentiation and activation during their lifetime. There is evidence of the presence of these innate CD8+ T-cells in the human umbilical cord, highlighting the necessity of investigating whether the NK-like CD8+ T-cells arise in the early stages of life (gestation). Based on the presence of cell surface markers, these cells have also been referred to as CD8+KIR+ T-cells, innate CD8+ T-cells, CD8+CD28−KIR+ T-cells or NKT-like CD8+CD56+ cells. However, the functional and co-signaling significance of these NK cell receptors on NK-like CD8+ T-cells is less clear. Also, the diverse array of co-stimulatory and co-inhibitory receptors are spatially and temporally regulated and may have distinct overlapping functions on NK-like CD8+ T-cell priming, activation, differentiation, and memory responses associated with different cell phenotypes. Currently, there is no consensus regarding the functional properties and phenotypic characterization of human NK-like CD8+ T-cells. Environmental factors, such as aging, autoimmunity, inflammation, viral antigen re-exposure or the presence of persistent tumor antigens have been shown to allow differentiation (“adaptation”) of the NK-like CD8+ T-cells; the elucidation of this differentiation process and a greater understanding of the characteristics of these cells could be important for their eventual in potential therapeutic applications aimed at improving protective immunity. This review will attempt to elucidate a understanding of the characteristics of these cells with the goal towards their eventual use in potential therapeutic applications aimed at improving protective immunity.